Использование номограмм для определения величин коэффициентов упитанности рыб - Тихонов, О.И. (Вестник зоологии, 1975)
A method is suggested to dermine the values of fatness coefficients based on T. W. Fulton's formula (1906) by means of nomograms, which leads to a 5-10-fold shortening of time for ordinary calculations. Determination of the fatness coefficient value consists in binding a point corresponding to the body weight of the given individual on one of the «dimension» straight lines. Projection of the point to the ordinate is the unknown quantity.